The Effect of Positive Affirmation Using Flashcards on The Anxiety of Laboring Women in The First Phase of Active Labor - Nayla Shaffira Aniq; Nana Usnawati; Dwi Purwanti; Kharisma Kusumaningtyas (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
Anxiety is a physical and psychological condition characterized by somatic, emotional, cognitive and behavioral components as a normal reaction resulting from stress. The purpose of this study is to find out the effect of providing positive confirmation using flashcards on the anxiety of active phase stage 1 delivery mothers.The research method uses Pre Experiment Design with research design One Group Pretest Postest. The sample was taken using a sample purposive technique of 35 active phase stage 1 mothers. The free variable of this study is positive affirmation using flashcards. The bound variable of this study is the anxiety of active phase stage 1 delivery mothers.Using the HARS instrument. With Wilcoxon test data analysis.Based on the research results, there was value p-value 0,000. From these results, there is an effect of providing positive confirmation using flashcards to active phase stage 1 delivery mothers. Giving positive affirmation use flashcard can reduce labor anxiety during the active phase of 1st stage. The research conclusion is that giving positive affirmations using flashcards can reduceanxiety during the first active phase. The mechanism of this method is able to influence the subconscious mind and can provide good suggestions for oneself.